The contribution of school culture to the learner success factors in e-learning - R. Chusnu Yuli Setyo; Suharsono Suharsono; Oikurema Purwati (Journal on English as a Foreign Language, 2018)
This study aimed to portray how a school culture contributed to the learner success factors in e-learning in the middle school level. The ethnographic case study design was applied to explore the school culture and the e-learning success factors more deeply and holistically. The data were collected through observations and in-depth interviews. The cross-case analysis was used to interpret the data. The subjects of the study were four students who won in the national e-learning competition and the setting of the institution was in SMP Tentara Genie Pelajar (TGP) in Malang. The fundamental finding of the study, that might not be found in other research, was that the high-academic performance culture of this school gave an indirect contribution to the students’ e-learning success factors, such as the students’ motivation, the students’ e-learning self-efficacy, the students’ prior knowledge on the e-learning technical competency, and the students’ interaction and collaboration. This study gave a big implication because an ethnographic case study on the e-learning critical success factors might be never done in Indonesia before.